Determinants of MSME Interest in Binjai City Using E-Payment as a Payment Method - Mutiara, Mutiara; Muliyani, Muliyani (Program Pascasarjana STIE Amkop Makassar, 2024)
This research was conducted on several MSMEs in Binjai City. The purpose of this research is to determine whether or not there is interest in of course MSMEs in Binjai City in using E-Payment services as a payment method by assessing perceived ease of use, perceived benefits and perceived risks. This research uses associative quantitative methods. This research is associative quantitative research (relationship or influence). Associative research is